Design and implementation of a user-centric swimming performance monitoring tool - Mullane, S. L.; Chakravorti, N.; Conway, P. P.; West, A. A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2011)
The current methods for measuring swimmer performance are time consuming and require substantial manual interaction. Inevitably, such techniques are prone to error or require a large amount of post-event processing. The aim of the research outlined in this paper is to design a novel performance analysis tool to monitor and measure swimmer performance using wireless technology previously developed at Loughborough University and determine how to communicate these data effectively to the coach in real time. The overall system effectiveness is reliant upon effective data collection, storage, and analysis. Providing the functionality to design an effective system requires robust technology, appropriate structures in persistent storage, and interface design to communicate the capability set to the user. This paper is focused on the development of a graphical user interface (GUI); a type of human-machine interface (HMI), to support users within the swimming domain. The computer integrated manufacture open system architecture (CIMOSA), generally applied as a form of business process modelling, has been used to structure the development of a user-centric, real-time monitoring system that supports the needs of the coaches, sports scientists, and swimmers. A methodology that uses the CIMOSA reference architecture as the foundation has been proposed and implemented to create a user-driven GUI that accommodates variation in requirements of user types in the swimming domain to optimize the performance analysis methods.